FRAKSI ETIL ASETAT KULIT BATANG FALOAK (Sterculia quadrifida R.Br ) MENGINDUKSI APOPTOSIS DAN SIKLUS SEL PADA SEL KANKER PAYUDARA T47D - Rollando Rollando; Kestrilia Rega Prilianti (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2017)
Faloak (Sterculia quadrifida R.Br) is one source of bioactive compounds that could be developed as chemotherapeutic agent. Empirically East Nusa Tenggara people use boiled water of faloak bark as a cure for hepatitis (types A, B, and C), and gastroenteritis. This study was performed to test anticancer activity fraction of n-hexane, ethyl acetate, ethanol, and methanol of ethanolic extract from faloak stem bark for the type of breast cancer cell line T47D, and normal cell types Vero using cytotoxic 3- (4,5-dimetilazol- 2-yl) -2,5-difeniltetrazolium bromide (MTT) test method. Ethanolic extract was subjected to column chromatography using different solvents polarity level as n-hexane, ethyl acetate, ethanol, and methanol. Testing the cytotoxic effects using the MTT assay in T47D breast cancer cells and normal Vero cells with EC50 parameter. Ethyl acetate fraction in inducing apoptosis and cell cycle modulation was observed with flowcytometry method. The test results cytotoxic fraction indicating the fraction of ethyl acetate has the lowest activity with EC50 of 24.88 ?g/mL and selectivity index of 15.58. Ethyl acetate fraction effects an accumulation of cells in S phase (27.43%) in breast cancer cells T47D which is able to induce apoptosis. These results demonstrate that the ethyl acetate fraction can be developed as a chemotherapeutic agent in improving the effectiveness of breast cancer treatment.